Effects of maxacalcitol ointment on skin lesions in patients with psoriasis receiving treatment with adalimumab. Issue 11 (23rd July 2016) - Karakawa, Masaru; Komine, Mayumi; Kishimoto, Megumi; Maki, Nobuki; Matsumoto, Ai; Sugai, Junichi; Ohtsuki, Mamitaro
Abstract: Adalimumab is a biologic that is very effective for treatment of psoriasis. However, recalcitrant or recurrent lesions sometimes occur during treatment. Maxacalcitol is an active vitamin D3 ointment that is effective in treatment of psoriasis. Topical therapy may be beneficial in treatment of recalcitrant or recurrent lesions during treatment with systemic therapy, but there is little evidence on this topic. We investigated the effect of maxacalcitol on skin lesions during treatment with adalimumab in patients with psoriasis. Twelve patients with psoriasis were randomly assigned to two groups after informed consent – treatment with adalimumab only ( n = 6), and treatment with adalimumab and maxacalcitol ( n = 6) – and they were evaluated every 4 weeks for 44 weeks. Exacerbation was defined as an increase of the Psoriasis Area and Severity Index (PASI) score. The interval between adalimumab treatments was elongated to 3–4 weeks from 2 weeks according to the individual patient's condition. The PASI score was evaluated every 4 weeks, and the frequency of exacerbations was counted. The overall improvement in PASI score was not statistically different between the two groups, but the frequency of exacerbations was significantly less in the maxacalcitol combination group compared with the adalimumab monotherapy group (Mann–Whitney U ‐test, P < 0.05). The better control of skin lesions in patients who elongated the interval of adalimumab administration was achieved in the maxacalcitol combination group compared with the adalimumab monotherapy group. Topical maxacalcitol treatment is effective and useful in controlling skin lesions in patients with psoriasis when used in combination with adalimumab.